1986
DOI: 10.1042/cs0700039
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical evidence for an increased and progressive deposition of collagen in lungs of patients with pulmonary fibrosis

Abstract: To assess the role of changes in lung collagen in pulmonary fibrosis, the content of this protein was measured in biopsy and autopsy lung from patients with cryptogenic fibrosing alveolitis (CFA), a fibrotic lung disorder of unknown cause. The collagen concentration was measured in lung samples from 21 patients with CFA (14 autopsy and seven open-lung biopsy) and 17 normal subjects; total lung collagen was determined in the right lung of 10 patients who died from CFA and the results were compared with those fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Our data suggest that lung collagen can be deposited in the lung of virally infected mice as early as 5 days post-infection. Although we are not proposing that influenza infection causes pulmonary fibrosis, it is evident that key mechanisms involved in the development of fibrosis, including ␣v␤6-mediated TGF␤ activation (4,68), epithelial apoptosis (25), and lung collagen deposition (69), are triggered by influenza infection and may thus promote fibrogenesis in an appropriately susceptible host. In conclusion, the results described herein provide a novel mechanism through which pulmonary infection with influenza virus can result in the activation of TGF␤ via a Smad3-, TLR3-, and ␣v␤6 integrin-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that lung collagen can be deposited in the lung of virally infected mice as early as 5 days post-infection. Although we are not proposing that influenza infection causes pulmonary fibrosis, it is evident that key mechanisms involved in the development of fibrosis, including ␣v␤6-mediated TGF␤ activation (4,68), epithelial apoptosis (25), and lung collagen deposition (69), are triggered by influenza infection and may thus promote fibrogenesis in an appropriately susceptible host. In conclusion, the results described herein provide a novel mechanism through which pulmonary infection with influenza virus can result in the activation of TGF␤ via a Smad3-, TLR3-, and ␣v␤6 integrin-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in active pulmonary fibrosis, the number of fibroblasts staining for procollagen and their average intracellular collagen content (and almost certainly their synthetic activity) is increased. Thus, it appears clear from this and related studies that unknown factors in pulmonary fibrosis stimulate both increased numbers offibroblasts and a more active fibroblast synthetic phenotype (1,3,21,22). Lung fibroblasts staining with Anti-pC could contain more procollagen than fibroblasts from quiescent lung simply because procollagen secretion is somehow impeded, as in the case of ascorbate deprivation (23).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in many cases the etiology is clear, cases are frequently of unknown cause, thus creating a significant therapeutic dilemma. Although the pathophysiologic mechanisms remain unclear, progressive connective tissue deposition characterizes fibrotic lung disorders (1). Histopathological and clinical findings currently guide therapy (2) but there is a clear need for more objective methods to assess disease activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Areas of dense collagen accumulation (old scar) are juxtaposed with fibroblastic foci (new scar formation). Collagen I and other minor isoforms (type III, V) are the primary components of the new abnormal matrix, [3][4][5][6] where the balance changes during progression. For example, previous studies have found that collagen III is characteristic of early IPF, whereas collagen I dominates in late-stage disease.…”
Section: Introductionmentioning
confidence: 99%